High Power Press-pack IGBT and Its Application in Pulsed Magnetic-field Generator - CHEN Jun; WAN Chaoqun; CHEN Yan; LI Xiaolin (Kongzhi Yu Xinxi Jishu)
In some special field of high voltage and high current, the application of conventional IGBT will increase the complexity of system structure and difficulties of control. Therefore, this paper introduced a new type of power press-pack IGBT device. Based on the proposed press-pack IGBT device, a press-pack IGBT stack was developed, consisting of 6 press-pack IGBTs and of 2S3P structure. Its maxim on-state duration is 10 s, persistent current and turn off current is 20 kA, and rated voltage is up to 6 600 V. The proposed IGBT stack has been applied in various fields, among which its application in pulsed magnetic-field generator is highlighted in this paper. To enhance conduction ability, the gate circuit design has been optimized, the quantity of IGBTs and turnoff overvoltage have also been reduced. Simulation results show the good performance of the proposed IGBT stacks, which can meet the requirements of pulsed magnetic-field generator.